Linguistic argumentation and logic: an alternative method approach in Arabic grammar - Yaacob, Solehah@Nik Najah Fadilah (2013)
This research emphasizes the relationship between linguistic argumentation1 and logic1. Linguistic argumentation is a language system which uses the meaning of expressions in a sentence to draw a complete meaning of the sentence, as there lies a dependence between expressions. In fact, this connection between expressions enhances the overall meaning from the very fundamentals of the sentence structure in the logical relationship between ideas; where there lies a relation between words and the mind which is dependent on the logic of combined utterances. In order to signify the above concept of thinking, the researcher has turned to the theory of the early system of Arabic grammar which focuses more on analogical approach rather than anomaly. The analogical approach in the system is based on the underlying theory which implies the aforementioned relationship, even though some modern views may disagree on the interpretation of this issue. To round out the discussion, the researcher has included similar existing theories on Latin grammar which have shown the logical approach to be a result of the connection between linguistic argumentation and logic. As a result of this discussion, the connection between words and logic is shown to be a universal concept.